Pembangunan Manusia melalui Optimalisasi Lembaga Pengelolaan Zakat - Adi Setiawan; Trisno Wardy Putra; Rizky Hariyadi (Management of Zakat and Waqf Journal (MAZAWA), 2020)
This study aims to reveal a conceptual strategy regarding the existence of zakat institutions as Islamic philanthropic institutions. The focus of this research concerns zakat and community development. This study intends to determine the role of zakat in enhancing development and strategies for zakat in overcoming community problems, especially economic welfare problems that have not been resolved. This research uses library research method, which examines various literatures or references related to zakat and community development by linking with existing theories and research as a form of accuracy of library research. The results of the discussion indicate that zakat is closely related to community development. The zakat strategy in overcoming community problems, namely: 1) increasing the number of property owners and changing the condition of most poor and poor people to become well-off people, or it can also be termed an economic migration from mustahiq to muzakki, 2) eliminating the nature of begging (chirity) ), 3) eliminating envy and enmity between Muslims, 4) coping with disasters, 5) repeating celibacy, 6) helping refugees.